Teaching sport concepts and skills. A tactical games approach for ages 7 to 18 - Mitchell, S. A.; Oslin, J. L.; Griffin, L. L. (Human Kinetics, 2013)
The third edition of the popular book Teaching Sport Concepts and Skills: A Tactical Games Approach for Ages 7 to 18 now covers the elementary level as well as middle and secondary levels. It shows teachers how to move from a traditional to a tactical games teaching approach with detailed unit and lesson plans, a DVD-ROM with video clips and reproducibles, and a standards-linked Game Performance Assessment Instrument (GPAI). Teaching Sport Concepts and Skills, Third Edition, not only explains the tactical games approach, but it also contains more than 330 ready-to-use lessons to help teachers apply it. Elementary school teachers will use games to teach the basic concepts and tactics of these types of sports: